2022
DOI: 10.1186/s12889-022-14440-x
|View full text |Cite
|
Sign up to set email alerts
|

The actual and anticipated effects of restrictions on flavoured electronic nicotine delivery systems: a scoping review

Abstract: Objective To synthesize the outcomes of policy evaluations of flavoured electronic nicotine delivery systems (ENDS) restrictions. Data sources PubMed, Scopus, Embase and Web of Science before May 3, 2022. Study selection Studies that report sales, behaviour, or compliance outcomes related to implemented or hypothetical ENDS flavour restrictions. Data extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
2
0
2
Order By: Relevance
“…Despite the potential issues raised, some participants were still supportive of flavour restrictions to discourage youth from initiating vaping. In line with these participants' opinions, after flavour restrictions were introduced in Finland, e-cigarette use has remained low among 15-to 69-year-olds [42], and the prevalence of e-cigarette use among young adults has decreased among young adults since the ban in San Francisco and other US states [13,54]. Other participants suggested that alternative measures could be more effective, and that there are other more important drivers of vaping behaviour than flavours, such as health concerns and trendiness.…”
Section: Discussionmentioning
confidence: 66%
“…Despite the potential issues raised, some participants were still supportive of flavour restrictions to discourage youth from initiating vaping. In line with these participants' opinions, after flavour restrictions were introduced in Finland, e-cigarette use has remained low among 15-to 69-year-olds [42], and the prevalence of e-cigarette use among young adults has decreased among young adults since the ban in San Francisco and other US states [13,54]. Other participants suggested that alternative measures could be more effective, and that there are other more important drivers of vaping behaviour than flavours, such as health concerns and trendiness.…”
Section: Discussionmentioning
confidence: 66%
“…Für klassische Filterzigaretten ging das 2009 erlassene Aromenverbot mit reduzierten Verkaufszahlen einher, während die Verkaufszahlen anderer aromatisierter Tabakprodukte, wie Zigarren und Zigarillos, anstiegen. Unklar ist bisher, wie sich Aromastoffe in E-Zigaretten auf den begleitenden Konsum von konventionellen Zigaretten auswirken [35]. Bei einer Untersuchung wurden Zigarettenrauchenden für eine Dauer von 6 Wochen E-Zigaretten angeboten.…”
Section: Humane Datenunclassified
“…Für klassische Filterzigaretten ging das 2009 erlassene Aromenverbot mit reduzierten Verkaufszahlen einher, während die Verkaufszahlen anderer aromatisierter Tabakprodukte, wie Zigarren und Zigarillos, anstiegen. Unklar ist bisher, wie sich Aromastoffe in E-Zigaretten auf den begleitenden Konsum konventioneller Zigaretten auswirken [35]. Bei einer Untersuchung wurden Zigarettenrauchenden für eine Dauer von 6 Wochen E-Zigaretten angeboten.…”
Section: Humane Datenunclassified